(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Microfinance in India has emerged as a critical tool for financial inclusion, poverty alleviation, and socio-economic development, particularly for marginalized communities. Over the past few decades, microfinance institutions (MFIs) have played a pivotal role in providing small loans, savings, insurance, and other financial services to individuals who lack access to formal banking systems. These services, primarily targeted at women, rural populations, and low-income households, have empowered individuals to start or expand small businesses, improve living standards, and invest in education and health.